Perebutan Air dan Ketidakberdayaan Kelompok Tani Dalam Menjaga Irigasi Studi Kasus di Padukuhan Bayen, Kabupaten Sleman Daerah Istimewa Yogyakarta - Muh Kamim, Anggalih Bayu; Dharmawan, Arya Hadi; Abdulkadir-Sunito, Melani; Yulian, Bayu Eka (Jayapangus Press, 2025)
This study analyzes the inability of “peasant organization” to control irrigation resources in rural-urban areas. Water disputes have arisen among peasants in rural-urban areas due to their limited capacity to organize themselves and manage available resources. This research seeks to examine the weaknesses in the role of peasant organizations in coordinating the use of irrigation resources. This study is a qualitative research using case study approach, focusing on Bayen sub-village, District of Sleman Special Region of Yogyakarta. The data collection process was done via in-depth interviews, documentation techniques, and field observation. The analyst’s work progressed from study preparation to data verification and conclusion. The research reveals that elite peasants have become central actors in water disputes, undermining the effectiveness of peasant organizations. Furthermore, both local and village governments fail to adequately support these organizations due to budgetary constraints and limited policymaking capacity. The “peasant organization” also does not have sufficient capacity to coordinate with other peasants in many different areas surrounding Bayen sub-village. The study shows that the bad condition of irrigation in Bayen sub-village is related to the lack of capacity of peasants to negotiate with different actors that have many different interests. Urban economic expansion led to the establishment of an ice factory, disrupting peasant irrigation systems. The toll road project, a consequence of urban economic expansion, has also disrupted irrigation systems in the region. As a result of these problems, the peasants, together with the head of Bayen sub-village, can only promote the use of toll drainage as an emergency irrigation measure.